Regional variation in alcohol consumption in the Northern Territory - Gray, Dennis; Chikritzhs, Tanya (2000)
Regional variation is studied in per capita consumption of alcohol and the types of beverages consumed in the Northern Territory of Australia in order to estimate the relative contributions to consumption by Aboriginal and non-Aboriginal people. Per capita consumption estimates were based on wholesale purchases of alcohol by licensee and Census population data. Mean levels and the percentages of each beverage type consumed were compared between regions and through time. Estimates of per capita levels of consumption between Aboriginal and non-Aboriginal segments of the population were based on reports of the proportion of frequent and occasional drinkers in each group and the ratio of onsumption among Aboriginal and non-Aboriginal drinkers. Mean quarterly per capita consumption was higher in both the Lower Top End (4.22 litres) and the Central NT (4.04 litres), and less in the Barkly (3.44 litres) than in the Top End (3.55 litres). Over the four-year period, consumption in the Top End rose 6.4%, but dropped 22.5% in the Barkly. In the Lower Top End and the Central NT a larger percentage of alcohol was consumed as cask wine than in the Top End. Before licensing restrictions were introduced, this was also the case iri the Barkly. In the NT, per capita consumption among Aboriginal people is approximately 1.97 times, and among nonAboriginal people about 1.43 times, the national average. It is concluded that lcohol consumption in the NT is greater than in Australia as a whole and there is significant regional variation. The problem is not simply an Aboriginal problem, and a broad range of strategies including a component to address regional variation - is required to reduce it.